Integration of Metabolome and Transcriptome Reveals the Relationship of Benzenoid–Phenylpropanoid Pigment and Aroma in Purple Tea Flowers - Mei, Xin; Wan, Shihua; Lin, Chuyuan; Zhou, Caibi; Hu, Liuhong; Deng, Chan; Zhang, Lingyun (Frontiers in Plant Science, 2021)
Tea (Camellia sinensis) flowers are normally white, even though the leaves could be purple. We previously discovered a specific variety with purple leaves and flowers. In the face of such a phenomenon, researchers usually focus on the mechanism of colour formation, but ignore the change of aroma. The purple tea flowers contain more anthocyanins which belong to flavonoids. Meanwhile, phenylalanine (Phe), derived from shikimate pathway, is a precursor for both flavonoids and volatile benzenoid-phenylpropanoids (BPs). Thus, it is not clear whether the BP aroma was attenuated for the appearance of purple colour. In this study, we integrated metabolome and transcriptome of petals of two tea varieties, Zijuan (ZJ) with white flowers and Baitang (BT) with purple flowers, to reveal the relationship between colour (anthocyanins) and aroma (volatile BPs). The results indicated that in purple petals, the upstream shikimate pathway was promoted for DAHPS (3-deoxy-D-arabino-heptulosonate 7-phosphate synthase) was elevated; Among the increased anthocyanins, delphinidin-3-O-glucoside (DpG) was extremely higher; Volatile BPs, including benzyl aldehyde, benzyl alcohol, acetophenone (AP), 1-phenylethanol and 2-phenylethanol, were also enhanced, and AP was largely elevated. The structural genes related to the biosynthesis of volatile BPs were induced while the whole flavonoid biosynthesis pathway was downregulated, except for the genes F3’H (flavonoid 3'-hydroxylase) and F3’5’H (flavonoid 3',5’-hydroxylase) which were highly expressed to shift the carbon flux to delphinidin, which were then conjugated to glucoside by increased BZ1 (UDP-glucose : flavonoid 3-O-glucosyltransferase) to form DpG. Transcription factors (TFs) highly related to AP and DpG were selected to investigate their correlation with the differentially expressed structural genes. TFs, such as MYB, AP2/ERF, bZIP, TCP and GATA, were dramatically expressed and focused on regulation of genes in the upstream synthesis of Phe (DAHPS; arogenate dehydratase/prephenate dehydratase), and the synthesis of AP (phenylacetaldehyde reductase; short-chain dehydrogenase/reductase), Dp (F3’H; F3’5’H) and DpG (BZ1), but inhibited the formation of flavones (flavonol synthase) and catechins (leucoanthocyanidin reductase). These results discovered an unexpected promotion of volatile BPs in purple tea flowers, and extended our understanding of the relationship between the BP-type color and aroma in tea plant.